Increase in FHA improvement loans - Guam and Hawaii housing amendment : hearing before a subcommittee of the Committee on Banking and Currency, United States Senate, Eighty-third Congress, first session on S.J. Res. 26, to extend certain authority of the Federal National Mortgage Association and the Federal Housing Administration to Guam and Hawaii ; S.J. Res. 27, to amend section 2 (A) of the National housing act, as amended, February 2[-5] 1953. - United States. Congress. Senate. Committee on Banking and Currency (Washington : U.S. G.P.O., 1953)
Considers legislation to expand FHA home improvement guaranteed loan program, and to expand FHA and FNMA housing programs in Hawaii and Guam.
[pt. 1]. On S.J. Res. 26 ... and S.J. Res. 27 ... February 2, 1953. -- pt. 2. On S.J. Res. 26 ... February 5, 1953.
Irving M. Ives, chairman of subcommittee.
Mode of access: Internet.
Keywords: Mortgage guarantee insurance; Housing -- Finance -- Law and legislation; Housing; Housing -- Guam; Housing -- Hawaii; Housing -- Finance -- Law and legislation -- United States; Mortgage guarantee insurance -- United States; United States; Hawaii; Guam